2013
DOI: 10.1021/ic302355b
|View full text |Cite
|
Sign up to set email alerts
|

Heptacoordinated Molybdenum(VI) Complexes of Phenylenediamine Bis(phenolate): A Stable Molybdenum Amidophenoxide Radical

Abstract: The syntheses, crystallographic structures, magnetic properties, and theoretical studies of two heptacoordinated molybdenum complexes with N,N′-bis(3,5-di-tert-butyl-2-hydroxyphenyl)-1,2-phenylenediamine (H 4 N 2 O 2 ) are reported. A formally molybdenum(VI) complex [Mo(N 2 O 2 )Cl 2 (dmf)] (1) was synthesized by the reaction between [MoO 2 Cl 2 (dmf) 2 ] and H 4 N 2 O 2 , whereas the other molybdenum(VI) complex [Mo(N 2 O 2 )(HN 2 O 2 )] (2) was formed when [MoO 2 (acac) 2 ] was used as a molybdenum source. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…For the ligand L bearing the o ‐phenylene bridge (Scheme 2), the oxidation states from 0 to −4 are accessible, which makes it an efficient electron reservoir. For this ligand, complexes with transition metals Ti, [13, 14] Zr, [14, 15] Hf, [13] Mo, [16] W, [17] Mn, [18] Cu, [19] and Zn, [19] as well as Sn [20] as the only post‐transition metal, are known. Catalytic properties of some of these complexes were studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ligand L bearing the o ‐phenylene bridge (Scheme 2), the oxidation states from 0 to −4 are accessible, which makes it an efficient electron reservoir. For this ligand, complexes with transition metals Ti, [13, 14] Zr, [14, 15] Hf, [13] Mo, [16] W, [17] Mn, [18] Cu, [19] and Zn, [19] as well as Sn [20] as the only post‐transition metal, are known. Catalytic properties of some of these complexes were studied.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Complexes with noninnocent redox-active ligands( most often, o-benzoquinones and o-iminoquinones) are also of interest for catalytic applications. [12] For the ligand Lb earing the o-phenylene bridge (Scheme 2), the oxidation states from 0t oÀ4a re accessible, which makes it an efficient electron reservoir.F or this ligand, complexes with transition metals Ti, [13,14] Zr, [14,15] Hf, [13] Mo, [16] W, [17] Mn, [18] Cu, [19] and Zn, [19] as well as Sn [20] as the only posttransition metal,a re known.C atalytic properties of some of these complexes were studied. It was found that the Ti complex is effective in the polymerisation of rac-lactide, [14] the Zr complexc atalyses the disproportionationo f1 ,2-diphenylhydrazine to azobenzene and aniline, [15] and the Cu and Zn complexes catalyse oxidation of primary alcohols by air.…”
Section: Introductionmentioning
confidence: 99%
“…[6] This potentially tetradentate ligand has a versatile electrochemical behavior as it can present five different oxidation states that are interrelated by one-electron transfer steps (see Chart 1). Once partially or fully deprotonated, H 4 N 2 O 2 can act as a multidentate ligand to form complexes with the early transition metals Ti, Zr and Hf [7][8][9] as well as the late transition metals Cu and Zn [6] in a 1:1 metal-to-ligand ratio whereas 1:2 complexes are formed with Mo [10], Mn [11] and Sn [12]. In some cases, coordination to the metal center is associated with an intramolecular reaction leading to the formation of a new noninnocent phenoxazinylate/phenoxylate ligand.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…For comparison, the corresponding molybdenum compound [Mo(N 2 O 2 )(HN 2 O 2 )] with a ligand radical shows a rather similar spectrum with g iso = 2.0087. [10] In solid state, complex 1 is paramagnetic with susceptibility χ mol = 1.7•10 -6 m 3 /mol at 2 K (χ mol = M•χ v /ρ, where ρ is the density, M is molar mass and χ v is volume magnetic susceptibility), as measured by a SQUID magnetometer. The temperature dependence of the susceptibility was also measured and the data fitted to the Curie law of localized moments, χ mol = C/(T-θ p ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In coordination chemistry, a ligand is referred as 'non-innocent' when it forms complexes where the oxidation state of the central atom cannot be absolutely defined [1]. For example, o-aminophenol N,N -bis(3,5-di-tertbutyl-2-hydroxy-phenyl)-1,2-phenylenediamine H 4 L (the oxidation states of L, Scheme 1) has a rich redox-chemistry and its complexing abilities towards transition metals, i.e., Ti, Zr, Hf, Mo, W, Mn, Co, Cu and Zn, have attracted substantial interest over the past few years [2][3][4][5][6][7][8]. Earlier studies show that this proligand can form complexes with various transition metals in 1:1 and 2:1 stoichiometry.…”
Section: Introductionmentioning
confidence: 99%